RESPONS PERTUMBUHAN DAN HASIL TANAMAN UBI JALAR (Ipomoea batatas L.) JINGGA MADU TERHADAP PUPUK TRICHOKOMPOS - Santi, Santi; Setyawan; Nasatul Asmiah, Nurul (Jurnal Ilmiah Mahasiswa Fakultas Pertanian, 2025)
This study aims to determine the response of growth and yield of orange honey sweet potato (Ipomoea batatas L.) to the application of Trichokompos fertilizer and to identify the dosage that provides the best yield. The study was conducted over six months, from December 2023 to May 2024, at the experimental plot STIPER Berau Campus, East Kalimantan. The design used was a factorial Randomized Block Design (RBD) with five levels of Trichokompos fertilizer dosage: T₀ (control), T₁ (0.75 kg/plot), T₂ (1.5 kg/plot), T₃ (2.25 kg/plot), and T₄ (3 kg/plot), each repeated five times. The observed parameters included stem diameter, number of tubers per plant, tuber weight per plant, tuber weight per plot, and tuber weight per hectare. The analysis results showed that the application of Trichokompos fertilizer did not give a significant response to all observed parameters. However, the highest tuber weight per hectare was 2.81 Mg.ha⁻¹ in treatment T₄. Environmental factors such as high rainfall and low light intensity were suspected to influence the results obtained. Trichokompost fertilizer has the potential to improve plant growth and yield through the improvement of soil physical properties and nutrient availability, but its effectiveness is highly influenced by environmental conditions and the dosage used. Further research is needed on the use of various doses of Trichokompos fertilizer and other factors on the orange honey sweet potato variety.